Mortality and the Business Cycle: Evidence from Individual and Aggregated Data - Gerard J. van den Berg; Ulf-G. Gerdtham; Stephanie von Hinke; Maarten Lindeboom; Johannes Lissdaniels; Jan Sundquist; Kristina Sundquist (Lund University, School of Economics and Management, Department of Economics, 2017)
There has been much interest recently in the relationship between economic conditions and mortality, with some studies showing that mortality is pro-cyclical, while others find the opposite. Some suggest that the aggregation level of analysis (e.g. individual vs. regional) matters. We use both individual and aggregated data on a sample of 20-64 year-old Swedish men from 1993 to 2007. Our results show that the association between the business cycle and mortality does not depend on the level of analysis: the sign and magnitude of the parameter estimates are similar at the individual level and the aggregate (county) level; both showing pro-cyclical mortality.
Keywords: E03; I10; I12; 330; Mortality; Recessions; Business Cycle; Health; Unemployment; Income.